Bioinspired Polarization Sensitive Photodetector System Using Orientation‐Tunable PDA Microfibers Arrays. Issue 11 (1st August 2016) - Liu, Yingying; Xia, Hongyan; Cheng, Junjie; Zou, Gang
Abstract : Polydiacetylene‐polystyrene (PDA‐PS) hybrid microfibers are prepared by electrospinning method. The intrinsic alignment PDA chains within the microfiber and the resulted polarization sensitive waveguide performance can be rigorously controlled by the polymerization process. PDA microfibers with different orientations can be assembled together to mimic the structure and function of natural rhabdome for detecting the polarization of the incoming light. Abstract : Most insect eyes use microvillar photoreceptors, where the visual pigment rhodopsin is aligned within tubular microvilli, endowing the insects with amazing navigation ability through detecting the polarization of illuminating light in the sky. Herein, polydiacetylene‐polystyrene (PDA‐PS) hybrid microfibers are fabricated by electrospinning method and it is demonstrated that PDA‐PS hybrid microfibers exhibit interesting polarized waveguiding properties, which is found to be dependent on the ordered alignment of PDA chains, but not on the propagating distance or the wavelength of the excitation light. Moreover, three PDA‐PS microfibers with different polarized waveguiding behavior can be assembled together as polarization sensitive photoreceptors to mimic the natural rhabdome arrays in insect eyes, since the physical dimensions, structure, and function of single PDA‐PS microfiber are comparable to that of natural rhabdomere.